The Implications of Artificial Intelligence in Marketing - Jalonen, Emma (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Technology has always been a driving force behind the development of marketing, and therefore the implications of the development and advancement of artificial intelligence (AI) in the field of marketing cannot be ignored. This study focuses mainly on the so-called “weak” AI that is already widely used in everyday life. AI applications use technologies such as computer vision, machine learning, natural language processing, robotics, and speech recognition. These technologies offer vast possibilities in marketing now and in the future. Marketing has evolved from the traditional 4Ps Marketing Mix towards a more customer-oriented field in a service-dominant digital world. This study aims to understand what kind of implications artificial intelligence technologies can have in the field of marketing. This main research objective was examined through three sub-objectives: (1) How can marketers/companies benefit from the use of AI technologies? (2) How can AI help in customer value creation? (3) What are the risks and limitations of the development and use of AI technologies in marketing? This exploratory study was conducted via qualitative semi-structured expert interviews and aimed to provide a wide overview of the topic. Three of the interviewees were experts in the field of marketing, and five were experts in various fields of computer science, technology and artificial intelligence. All interviews were conducted in Finnish, recorded, transcribed into text and then translated into English during analysis. There were several implications of artificial intelligence in the field of marketing that were identified and discussed in this study. The most significant benefits from the use of AI technologies identified for companies and marketers were: increased efficiency or better performance, cost-effectiveness, optimisation, automation, data analysis, better targeting, and mass personalisation. The ways in which AI can help in customer value creation are currently mainly lower-level utilitarian and financial value, like lower prices, more efficiency, better targeting and a feeling of being engaged and more connected to the brand. In the future, there is potential for more. The risks and limitations of the development and use of AI technologies in marketing are currently mostly related to AI technologies not being quite developed enough. From the marketers’ perspective, there is also a risk of loss of jobs. From the consumer’s point of view the main threats are cyber security and data protection. This study is limited in scope and scale and further research is recommended to delve deeper into the various aspects of this topic.